Helmet use among motorcycle accident victims in the north-east region of Jamaica. Issue 4 (2nd October 2019) - Fletcher, Cary; McDowell, Derrick; Thompson, Camelia; James, Kenneth
Abstract: Currently in Jamaica, motorcyclists account for the largest group of fatalities among all road users. Between 2016 and 2018, a cross sectional study was conducted at the Saint Ann's Bay Regional Hospital involving 155 participants. There were 98.7% males, ages ranged from 14-64 years and more than two thirds of the motorcyclists were under 40 years. Only 29.4% wore helmets, and of those motorcyclists, 52.8% indicated they were only riding for a short distance. Increasing age correlated with increased helmet compliance. Persons with motorcycles greater than 150 cubic centimetres were also more likely to wear a helmet. Interventions to promote increased helmet compliance should take these factors into account in conjunction with enhancing law enforcement.